Mentoring Programmes: Supporting Effective Technology Use in Transpare ncy and Accountability Organisations - Herringshaw, Vanessa; Faith, Becky (Transparency & Accountability Initiative, 2015)
The global movement to hold governments and companies accountable is g rowing rapidly, and technology can play a vital role. Some actors harn ess this potential to brilliant effect. But many others waste precious money and staff time on technology that isn’t a good fit for their ai ms or capacity. Mentorships can be a really effective way …